Ideology and architecture of the Francois Rabelais’s Abbey of Thélème - Жилін, Михайло Володимирович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article provides a comparative analysis of the utopian urban planning in the literary and philosophical works of Plato, Thomas More, Rabelais, Tommaso Campanella and Francis Bacon. The final episode of the Rabelais’s novel “Gargantua”, in which Rabelais gives a description of the ideal abbey, seen as the first in the history of European fiction architectural project, not subject to a specific supreme idea. Abbey of Thélème is a subordinate only to the laws of aesthetics utopia.